Analisis Pendapatan Dan Biaya Kaitannya Dengan Penyajian Laba Kotor PT. Jatropha Oil Indonesia - Rosita, Siti Ita; S, Ribut Yudi (Institut Bisnis dan Informatika Kesatuan, 2016)
Revenues generally classified as one that resourced from company’s normal activities and one that is not. Revenues resulted from normal activities usually obtained from goods or services selling relating to company’s main activities. Expenses are deducting factors of revenues to obtain profits and/or loss. Expenses arised form company’s activities are consisted of production costs, business costs and other costs. Gross profits is more actually operative in character when compared to operating profit, Even though gross profit is often perceived to normally depicting company’s normal activities, not all costs reflected in operating costs are directly related to the creation of revenues. The research is to analyse revenues and expenses recognition in a manufacturing company. Analysis is conducted to investigate whether or not the recognition of expenses and revenues run by the company is accountable to compile gross profit and then be used to evaluate the production department performance. The result shows that the company has properly recognised the revenues obtained, but not in the expenses part. This is due to the improper method used.